HUBUNGAN STATUS PERIODONTAL DAN DERAJAT REGULASI GULA DARAH PASIEN DIABETES MELITUS DI RUMAH SAKIT UMUM PUSAT PROF DR. R. D. KANDOU MANADO - Emor, Stephanie F.; Pandelaki, Karel; Supit, Aurelia S. R. (e-GiGi, 2015)
Abstract: Diabetes mellitus (DM) is a disorder characterized by hyperglycemia and impaired metabolism of carbohydrates, fats, and proteins. These are caused by insulin deficiency, relative or absolute. Diabetes mellitus is a long-term chronic disease with a risk of the occurence of diabetic complications, such as oral diabetic. The study aimed to analyze the relationship between periodontal status and the degree of blood sugar regulation in diabetic patients in Prof. Dr. R. D. Kandou Hospital Manado. Data were obtained from the Endocrine clinic of Prof. Dr. R. D. Kandou Hospital. This was a descriptive analytical study with a cross sectional approach. Samples consisted of 37 patients (total sampling) aged 20-60 years. The analytic methods used in this study was the chi-square test (univariate and bivariate). Periodontal pocket depths were clinically examined. The results showed that there was no healthy periodontal state among diabetic patients. Uncontrolled diabetic patients with poor HbA1c (17 patients, 46%) had bad periodontal status. The chi-square test showed that there was a significant relationship between periodontal status and the degree of blood sugar regulation in diabetic patients (p < 0.05). Conclusion: There was a significant relationship between periodontal status and the degree of blood sugar regulation in diabetic patients.Keywords: periodontal status, diabetes mellitus, degree of regulation blood sugar.Abstrak: Diabetes melitus (DM) adalah kelainan yang ditandai hiperglikemia dan gangguan metabolisme karbohidrat, lemak, dan protein yang disebabkan oleh kekurangan hormon insulin secara relatif maupun absolut. DM merupakan penyakit kronis yang bila diabaikan dapat terjadi komplikasi diabetic, antara lain oral diabetic. Penelitian ini bertujuan untuk menganalisis hubungan status periodontal dan derajat regulasi gula darah pasien diabetes melitus di RSUP Prof. Dr. R. D. Kandou Manado. Pengumpulan data dilakukan di Poliklinik Endokrin RSUP Prof. Dr. R. D. Kandou. Penelitian ini bersifat deskriptif analitik dengan pendekatan potong lintang. Besar sampel sebanyak 37 orang (total sampling) usia 20-60 tahun. Analisis data secara univariat dan bivariat (uji chi-square). Pemeriksaan kedalaman poket periodontal dilakukan terhadap subjek penelitian. Hasil penelitian menunjukkan tidak adanya status periodontal yang sehat pada pasien DM. Pasien DM dengan HbA1c yang buruk memiliki status periodontal yang buruk pula yaitu sebanyak 17 pasien (46%). Berdasarkan hasil uji chi-square terdapat hubungan bermakna antara status periodontal dan derajat regulasi gula darah (p < 0,05). Simpulan: Terdapat hubungan bermakna antara status periodontal dan derajat regulasi gula darah pasien diabetes melitus.Kata kunci: status periodontal, diabetes melitus, derajat regulasi gula darah